Technological Transformation on Consumer Behavior: A Review of the Beauty Industry - Anggraini, Novy; Boros, Anita (Acta Carolus Robertus, 2024)
The industrial revolution changed consumer behavior in shopping. Online shopping has now become a lifestyle nowadays, not only for primary needs but also for cosmetics and personal care. Consumers emphasize more to the sustainability issues of the products they want to buy. Consumers are also becoming increasingly concerned and aware of the negative impacts caused by the use of cosmetics. This issue has gained consumers' awareness and made them switch to cosmetics made from natural ingredients. However, there is a lack of research contributions to the sustainability of natural cosmetics, especially those related to consumer behavior in online shopping. There must be a stronger focus on digital marketing strategy analysis regarding consumer behavior in shopping for natural cosmetics and the influence of the internet on the dissemination of information about these products and their benefits for humans and the environment. Suggestions must be implemented at the company level in order to create a digital marketing strategy to expand the market and reach more consumers. At the institutional level, it can add research references related to this field.